Prospective Comparison of Acute Kidney Injury During Treatment With the Combination of Piperacillin-Tazobactam and Vancomycin Versus the Combination of Cefepime or Meropenem and Vancomycin. (April 2017) - Peyko, Vincent; Smalley, Samantha; Cohen, Henry
Purpose: To prospectively evaluate the observed incidence of acute kidney injury (AKI) in adult patients receiving the combination of piperacillin-tazobactam and vancomycin versus the combination of cefepime or meropenem and vancomycin for greater than 72 hours. Methods: This was a prospective, open-label cohort study at a community academic medical center involving adult patients over a 3-month time period who received either the combination of piperacillin-tazobactam and vancomycin or the combination of cefepime or meropenem and vancomycin for greater than 72 hours. The patients were evaluated for AKI, defined using specific criteria introduced by Kidney Disease: Improving global outcomes (KDIGO) acute kidney injury work group in 2012. Results: A total of 85 patients receiving either antimicrobial combination were evaluated for AKI. The incidence of AKI was significantly higher in the piperacillin-tazobactam and vancomycin group (37.3%) compared with the cefepime or meropenem and vancomycin group (7.7%; χ 2 = 7.80, P = .005). Conclusion: The result of this study suggests that the risk of developing AKI is increased in patients receiving the combination of piperacillin-tazobactam and vancomycin versus those receiving the combination of cefepime or meropenem and vancomycin.